Hybrid parallel strategy for the simulation of fast transient accidental situations at reactor scale. (August 2015) - Faucher, V.; Galon, P.; Beccantini, A.; Crouzet, F.; Debaud, F.; Gautier, T.
Highlights: Reference accidental situations for current and future reactors are considered. They require the modeling of complex fluid–structure systems at full reactor scale. EPX software computes the non-linear transient solution with explicit time stepping. Focus on the parallel hybrid solver specific to the proposed coupled equations. Abstract: This contribution is dedicated to the latest methodological developments implemented in the fast transient dynamics software EUROPLEXUS (EPX) to simulate the mechanical response of fully coupled fluid–structure systems to accidental situations to be considered at reactor scale, among which the Loss of Coolant Accident, the Core Disruptive Accident and the Hydrogen Explosion. Time integration is explicit and the search for reference solutions within the safety framework prevents any simplification and approximations in the coupled algorithm: for instance, all kinematic constraints are dealt with using Lagrange Multipliers, yielding a complex flow chart when non-permanent constraints such as unilateral contact or immersed fluid–structure boundaries are considered. The parallel acceleration of the solution process is then achieved through a hybrid approach, based on a weighted domain decomposition for distributed memory computing and the use of the KAAPI library for self-balanced shared memory processing inside subdomains.